Editorial: Nurses and Their Role in Managing The NonCommunicable Diseases - Malini, Hema (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Editorial: Nurses and Their Role in Managing The NonCommunicable Diseases